Social demand and preferences of university institutions. La Libertad Region, 2017 (SCIÉNDO INGENIUM, 2021)
The present study carried out by the National University of Trujillo (UNT) in La Libertad Region, aims to determine the social demand and the preference of university institutions that offer services in the Region. The design used was descriptive, cross-sectional, survey type, the study population was students of 4th and 5th grades of secondary education and parents. The three-stage random sampling was applied, selecting 6 provinces of the Region, then 365 educational institutions and, of these, a sample of 3438 students from the population under study and 671 from the population of parents. The application of structured questionnaires allowed us to obtain as a result that the UNT is the institution with the highest preference with 64,8% by students and 70,6% by parents; Likewise, the preference of students to apply to a public university was 61,2% and among parents, the preference was 70,6%. The preference percentages for specific careers were also obtained. The results will be very useful to make decisions about the social demand and university educational offer in La Libertad Region.
Keywords: Social demand; university institutions; preference; La Libertad Region